Unsafe Ground - Jonathan Paul Mitchell (The Royal Danish Library, 2021)
This paper discusses how everyday technologies contribute to the enaction of disability, in particular by continually frustrating the formation of a general sense of ease in the world. It suggests that bodies have a fundamental relationality, within which technology comprises a central aspect; and that the very entity called the human is constituted through relationships with technologies. Then, it considers two ways that the organisation of technology is involved in the realisation of both ability and disability. First, it describes how the distribution of technological resources for activity are centred around bodies that are attributed normality and correctness, which also de-centres bodies falling outside this category: the former are enabled to act while the latter are not. Second, it proposes that ability and disability also involve habit: activities that have not only been repeated until familiar, but in which body and technologies can be forgotten. That typical bodies are centred allows them to develop robust habitual relationships with technological environments in which body and technologies can recede from attention, and crucially, to acquire a sense that their engagements will generally be supported. Atypical bodies, as de-centred, lack this secure ground: they cannot forget their relations with environments, and cannot simply assume that these will support their activity. This erodes bodily confi dence in a world that will support the projects, whether ordinary or innovative, that constitute a life.